Advances in Structural Biology of ACE and Development of Domain Selective ACE-inhibitors - Polakovičová, Mája; Jampílek, Josef (Medicinal chemistry (Shariqah (United Arab Emirates)), 2019)
BACKGROUND: The Angiotensin-I converting enzyme (ACE) is one of the most important components of the renin-angiotensin-aldosterone system controlling blood pressure and renal functions. Inhibitors of ACE are first line therapeutics used in the treatment of hypertension and related cardiovascular diseases. Somatic ACE consists of two homologous catalytic domains, the C- and N-domains. Recent findings have shown that although both domains are highly homologous in structure, they may have different physiological functions. The C-domain is primarily involved in the control of blood pressure, in contrast to the N-domain that is engaged in the regulation of hematopoietic stem cell proliferation. The currently available ACE inhibitors have some adverse effects that can be attributed to the non-selective inhibition of both domains. In addition, specific Ndomain inhibitors have emerged as potential antifibrotic drugs. Therefore, ACE is still an important drug target for the development of novel domain-selective drugs not only for the cardiovascular system but also for other systems. OBJECTIVE: Detailed structural information about interactions in the protein-ligand complex is crucial for rational drug design. This review highlights the structural information available from crystallographic data which is essential for the development of domain selective inhibitors of ACE. METHODS: Over eighty crystal complexes of ACE are placed into the Protein Database. An overview of X-ray ACE complexes with various inhibitors in C- and N-domains and an analysis of their binding mode have given mechanistic explanation of the structural determinants of selective ligand binding. In addition, ACE domain selective inhibitors with dual modes of action in complexes with ACE are also discussed. CONCLUSION: Selectivity of ACE inhibitors for the N- and C-domain is controlled by subtle differences in the amino-acids forming the active site. Reported studies of crystal complexes of inhibitors in the C- and N-domains revealed that most selective inhibitors interact with non-conserved amino-acids between domains and have distinct interactions with the residues in the S2 and S2' subsites of the ACE catalytic site. Moreover, unusual binding of the second molecule of inhibitors in the binding cavity opens new possibilities of exploiting more distant regions of the catalytic center in structure-based design of novel drugs.
Keywords: Angiotensin converting enzyme (ACE); Catalytic Domain; Peptidyl-Dipeptidase A; Angiotensin-Converting Enzyme Inhibitors; angiotensin konvertující enzym; Humans; Substrate Specificity; Protein Binding; krystalografie rentgenová; inhibitory ACE; N-domain; Crystallography, X-Ray; lidé; proteinové domény; C-domain; zvířata; Drug Design; non-prime binding; substrátová specifita; katalytická doména; selective inhibitor.; vazba proteinů; racionální návrh léčiv; Protein Domains; Animals; crystal structure